DESIGN OF FEEDER PORT STRUCTURE AT WONRELI, MALUKU - Haniffullah, Zanuarto
Wonreli Port was built on Kisar Island in Wonreli District, Southwest Maluku Regency, Maluku Province. Wonreli Port is developed to adequately carry out goods and passenger loading and unloading activities which increase from each year. Wonreli Port itself is a feeder port with cargo handling in the form of general cargo. The developed port consists of docks and trestles with deck on pile type. The Final Project discussion includes an explanation of the criteria for dock structure and trestle design, collection and processing of environmental data, calculation of loads that work on docks and trestles, determination of dock and trestle dimensions, dock structure analysis, structural reinforcement design, and calculation of soil carrying capacity. The general reference to dock design is from the British Standard (BS) 6349 document: Marine Structure. While the calculation of the design of the pier's concrete structural elements refers to SNI 03-2847-2013. Analysis of the structure of the pier was carried out with the help of structural analysis software. The results of structural analysis software are in the form of unity check ratio (UCR), structural deflection, style in structure and laying reaction. Pier structure and trestel design is done by examining the value of UCR which is between 0.8 to 1, checking the deflection value with a value below the specified permit limit to obtain an optimal and economical structure. The results of the final assignment in the form of dock design and trestel include the dimensions of the dock structure with a length of 130 m and a width of 9.6 m. The dimensions of the Trestel structure are 90 m long and 5 m wide. The dimensions of structural elements are in the form of detailed reinforcement of the structural elements, and the design depth of the plan is as far as 13 m from the seabed.